2021
DOI: 10.48550/arxiv.2109.12945
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generation of high winding-number superfluid circulation in Bose-Einstein condensates

Abstract: We experimentally and numerically demonstrate a method to deterministically generate multiplyquantized superfluid circulation about an obstacle in highly oblate Bose-Einstein condensates (BECs). Our method involves spiraling a blue-detuned laser beam, which acts as a repulsive optical potential, around and towards the center of the BEC. This optical potential serves first as a repulsive stirrer to initiate superflow within the BEC, and then as a pinning potential that transports the center of the superfluid ci… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…[22][23][24][25][26]. Laser stirring is also employed to generate controlled vortex distributions [27][28][29]. A number of theoretical studies was reported in Refs.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26]. Laser stirring is also employed to generate controlled vortex distributions [27][28][29]. A number of theoretical studies was reported in Refs.…”
Section: Introductionmentioning
confidence: 99%